Reimarochloa (Gramineae: Panicoideae) en América Central: notas fitogeográficas y citológicas - Pohl, Richard W. (1974)
The genus Reimarochloa was previously not known from the North American continent. Reimarchloa brasiliensis is reported from El Salvador and Honduras. The plants are entirely cIeistogamous. Their foliar anatomy is panicoid. The somatic chromosome number is 2n = 20, this being the first count for the genus.